2021
DOI: 10.15393/j12.art.2021.3701
|View full text |Cite
|
Sign up to set email alerts
|

Phraseological Units as a Way to Compare Russian and Swedish Linguistic Worldviews

Abstract: This article discusses phraseological units in the Russian and Swedish languages. Phraseological units preserve distilled knowledge about culture, way of life, and history of peoples, and therefore give a holistic picture of their worldviews. One of the most frequently used components in phraseological units is the colorative component. The article analyzes and compares the meanings of Russian and Swedish phraseological units that contain the names of different colors, namely green, blue, yellow, red, pink, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The comparative study of the gender representation in Tatar and English phraseological units revealed that the female component in both languages frequently conveys a negative connotation (Khuzina & Mukhtarova, 2018). Comparison of Russian and Swedish phraseological units with the colour component showed that most of them characterise human beings, with less than 20% possessing positive connotation (Konovalova & Basova, 2021). In fact, the overwhelming majority of phraseological units possess the axiological component (Markelova et al, 2016;Kotova & Raina, 2020).…”
Section: Review Papermentioning
confidence: 99%
“…The comparative study of the gender representation in Tatar and English phraseological units revealed that the female component in both languages frequently conveys a negative connotation (Khuzina & Mukhtarova, 2018). Comparison of Russian and Swedish phraseological units with the colour component showed that most of them characterise human beings, with less than 20% possessing positive connotation (Konovalova & Basova, 2021). In fact, the overwhelming majority of phraseological units possess the axiological component (Markelova et al, 2016;Kotova & Raina, 2020).…”
Section: Review Papermentioning
confidence: 99%